Broomrapes (Orobanche spp.) the Challenge and Management: A review - Qasem, Jamal R. (Jordan Journal of Agricultural Sciences, 2021)
Broomrapes (Orobanche spp.) are among the most damaging parasitic weeds to agriculture. The subsite themselves on the roots of a wide range of cultivated and wild-grown plant species of different plant families. These parasites are varied in morphology and plant hosts they attack, although they share a large number of host species. Certain Orobanche species are more specialized to plant species of specific growth forms such as fruit and forestry trees. All Orobanche species are obligatory parasites because they lack chlorophyll and thus heterotrophic completely depend on host plants for food and/or water absorbed through specialized organs called a haustoria. The present review introduces information on biology, ecology, distribution, host/parasite relationship, economic importance, and management of the most important Orobanche species widely spread in Jordan and worldwide that cause great yield loss of different economic crops and devastate yield totally under heavy infestation. Recent literature and overview information on methods of control followed in Jordan and different parts of the world are included and discussed.